PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: STUDI KASUS HOTEL TRUNTUM PADANG - Riska Afrinida; Zusmawati Zusmawati (LP2M Universitas Bina Bangsa, 2024)
The aim of this research is to examine the influence of work motivation and work discipline on employee performance at Hotel Truntum Padang. The variables used in this study include the dependent variable, which is employee performance (Y), and the independent variables, namely work motivation (X1) and work discipline (X2). The type of this research is quantitative method, data collection through questionnaire distribution to 118 respondents using total sampling technique. By conducting instrument test (validity test and reliability test), assumption test (normality test, multicollinearity test, and heteroskedasticity test) then multiple linear regression and hypothesis testing with the help of SPSS application. The results of this study indicate that work motivation has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance